How sociable is your university brand? An empirical investigation of university social augmenters’ brand equity - Ahmed Eldegwy (18090610) (2018)
Purpose The purpose of this paper is to integrate branding and higher education literature to conceptualize, develop, and empirically examine a model of university social augmenters’ brand equity. Design/methodology/approach Drawing on an empirical survey of 401 undergraduate students enrolled in private universities in Egypt, this study model was tested using structural equation modeling. Findings The findings reveal that university social augmenters’ reputation, coach-to-student interactions, and student-to-student interactions influence students’ satisfaction with social augmenters. The results also suggest that students satisfied with university social augmenters are more likely to exhibit outcomes of brand equity – namely, brand identification, willingness to recommend, and willingness to incur an additional premium cost. Practical implications The results offer managerial implications for university administrators in their quest to enrich students’ university experiences and build strong sub-brands within the university setting. University social augmenters are found to have strong brand equity manifestations and may hold the potential to differentiate university brands in an industry dominated by experience and credence. Originality/value This research contributes to the extant literature by filling two gaps in university branding literature. First, previous research has never unified separate streams of literature related to augmented services and brand equity. Second, limited conceptual and empirical research on university branding in general and university social augmentation in particular has been conducted in emerging markets, which has resulted in conceptual ambiguity for the key factors constructing students’ university social experiences. Other Information Published in: International Journal of Educational Management License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1108/ijem-12-2017-0346